A systematic review and meta-analysis of sex differences in clinical outcomes of hypertrophic cardiomyopathy - Liu, Guyue; Su, Li; Lang, Mingjian (Frontiers in Cardiovascular Medicine, 2023)
Background Hypertrophic cardiomyopathy (HCM) is recognized as the most prevalent form of genetic cardiomyopathy, and recent investigations have shed light on the existence of sex disparities in terms of clinical presentation, disease progression, and outcomes. Objectives This study aimed to systematically review the literature and perform a meta-analysis to comprehensively compare the clinical outcomes between female and male patients with HCM. Methods A thorough search was conducted in databases including PubMed, Embase, Cochrane Library, and Web of Science, encompassing literature from inception until June 2023. The primary endpoints examined were: (1) all-cause mortality; (2) an arrhythmic endpoint comprising sudden cardiac death (SCD), sustained ventricular tachycardia, ventricular fibrillation, or aborted SCD; and (3) a composite endpoint incorporating either (1) or (2), in addition to hospitalization for heart failure or cardiac transplantation. Pooled estimates were derived using a random-effects meta-analysis model. Results The analysis encompassed a total of 29 observational studies, involving 44,677 patients diagnosed with HCM, of which 16,807 were female. Baseline characteristics revealed that the female group exhibited an advanced age [55.66 ± 0.04 years vs. 50.38 ± 0.03 years, pooled mean difference (MD) = 0.31, 95% CI: 0.22–0.40, p = 0.000, I2 = 88.89%], a higher proportion of New York Heart Association class III/IV patients [pooled odds ratio (OR) = 1.94, 95% CI: 1.55–2.43, p = 0.000, I2 = 85.92%], and a greater prevalence of left ventricular outflow tract gradient greater than or equal to 30 mmHg (pooled OR = 1.48, 95% CI: 1.27–1.73, p = 0.000, I2 = 68.88%) compared to the male group. The female group were more likely to have a positive genetic test (pooled OR = 1.27, 95% CI: 1.08–1.48, p = 0.000, I2 = 42.74%) and to carry the myosin heavy chain beta 7 mutation (pooled OR = 1.26, 95% CI: 1.04–1.54, p = 0.020, I2 = 0.00%) compared to the male group. Female sex exhibited a significant association with increased risks of all-cause mortality (pooled OR = 1.62, 95% CI: 1.38–1.89, p = 0.000, I2 = 72.78%) and the composite endpoint (pooled OR = 1.47, 95% CI: 1.20–1.79, p = 0.000, I2 = 84.96%), while no substantial difference was observed in the arrhythmic endpoint (pooled OR = 1.08, 95% CI: 0.87–1.34, p = 0.490, I2 = 55.48%). Conclusions The present findings suggest that female patients with HCM tend to experience poorer clinical outcomes. It is imperative to critically reevaluate disease definitions and enhance awareness to mitigate delays in the diagnosis and treatment of HCM in women, thereby fostering equitable healthcare practices. Systematic Review Registration https://www.crd.york.ac.uk/, PROSPERO (CRD42023431881).